2020
DOI: 10.3390/molecules25122942
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Classification and Authentication of Turmeric and Curry Samples by Targeted LC-HRMS Polyphenolic and Curcuminoid Profiling and Chemometrics

Abstract: The importance of monitoring bioactive substances as food features to address sample classification and authentication is increasing. In this work, targeted liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) polyphenolic and curcuminoid profiles were evaluated as chemical descriptors to deal with the characterization and classification of turmeric and curry samples. The profiles corresponding to bioactive substances were obtained by TraceFinderTM software using accurate mass databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…For instance, the presence of curcumin and other curcuminoids in turmeric-based extracts was confirmed using this strategy. As can be seen in Figure 5, the accurate mass spectra obtained by LC-HRMS with an orbitrap analyzer gave the authors reliable information for the identification of curcumin and other major components in the studied samples [82].…”
Section: Chromatographic Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, the presence of curcumin and other curcuminoids in turmeric-based extracts was confirmed using this strategy. As can be seen in Figure 5, the accurate mass spectra obtained by LC-HRMS with an orbitrap analyzer gave the authors reliable information for the identification of curcumin and other major components in the studied samples [82].…”
Section: Chromatographic Methodsmentioning
confidence: 73%
“…For instance, the presence of curcumin and other curcuminoids in turmeric-based extracts was confirmed using this strategy. As can be seen in Figure 5, the accurate mass spectra obtained by LC-HRMS with an orbitrap analyzer gave the authors reliable information for the identification of curcumin and other major components in the studied samples [82]. By far, ESI is the most generalized ionization source, although atmospheric-pressure chemical ionization (APCI) has also been proposed, especially for those compounds exhibiting low ionization efficiencies under ESI conditions [83][84][85].…”
Section: Chromatographic Methodsmentioning
confidence: 88%
“…Similarly, the MS 2 profile in negative mode revealed a characteristic peak with m / z 119 [M−H−44] – attributed to the removal of the CO 2 molecule, which further eliminated ethyne to generate a product ion with m / z 93 [M−H−CO 2 −C 2 H 2 ] – . Thus, compound 2 was annotated as 4-hydroxycinnamic acid, which was already observed in C. longa L. [ 37 ]. Compound 3 showed a protonated molecule with m / z 195.0657 [M+H] + .…”
Section: Resultsmentioning
confidence: 99%
“…Next, control had 114.22 lg/g, followed by cardamom and ginger with 93.79 and 89.99 lg/g, respectively. Indeed, Tanvir et al (2017) andN uñez et al (2020) have demonstrated that turmeric is rich in polyphenols and flavonoids, which have multiple health benefits. The correlation between ACL and ACW and total phenolic acids and flavonoids was 0.75, which suggests that these bioactive compounds are responsible for the antioxidant activity of kale crisps.…”
Section: The Content Of Phenolic Acids and Flavonoids In Kale Crispsmentioning
confidence: 99%